Discovering pattern of space layouts from low-income housing: A discussion of the New Normal preparedness after the Covid-19 pandemic. Issue 1 (1st March 2022) - Yahya, A S; Ahmad, M H; Hassan, A A G
Abstract: By the end of 2021, it is expected that the coronavirus (COVID-19) will shift from pandemic to endemic phase as the number of vaccinated people is increasing over time. It gives us hope as the endemic phase will allow us to live together with the virus. During the Covid-19 situation, people have become more creative and innovative for familiarising themselves with the New Normal. The next question is how is the existing housing for the low-income group ready to be suited with this situation? Therefore, this study will examine the concept of space design in housing units for the lower income group. The study adopted a case study approach based on housing layout from Kuala Lumpur, Bandung and Buckinghamshire. These housing layouts were analysed using the Space Syntax method for describing the meaning of space layout from a low-income perspective. This study found two consideration points, (1) the willingness of space to accommodate small business activities and to avoid the spread of epidemics in the domestic space, and (2) the willingness of the government to educate the public to cultivate small home entrepreneurship with the existing low-income routine and limited domestic spaces.